2021
DOI: 10.4236/ojemd.2021.115009
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness of Caregivers about Diabetic Ketoacidosis among Type-1 Diabetic Children and Their Action and Response in Riyadh City

Abstract: Objectives: Diabetic ketoacidosis (DKA) is a life-threatening metabolic disorder in which its complications can be avoidable. The purpose of this study is to identify and measure the level of knowledge and awareness of caregivers about the symptoms of DKA in children in Riyadh city. Setting and Participants: This cross-sectional study design was conducted in Riyadh city in Saudi Arabia. A sample size of at least 412 was required. The total number of respondents that were included in the analysis was 414. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Approximately 47.5% of the participants lacked awareness of DKA, while 10% provided incorrect answers, indicating a significant deficit in knowledge regarding this life-threatening complication of DM. Also, our study revealed a higher lack of knowledge compared to previous studies conducted in Sudan and Riyadh [6][7][8] where 21.8%, 33%, and 35.3% of the participants respectively indicated a lack of awareness of DKA. Moreover, our study highlighted that 33.8% of participants believed that forgetting to take insulin injections was a leading cause of DKA, highlighting a serious misunderstanding of a major contributing risk factor.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Approximately 47.5% of the participants lacked awareness of DKA, while 10% provided incorrect answers, indicating a significant deficit in knowledge regarding this life-threatening complication of DM. Also, our study revealed a higher lack of knowledge compared to previous studies conducted in Sudan and Riyadh [6][7][8] where 21.8%, 33%, and 35.3% of the participants respectively indicated a lack of awareness of DKA. Moreover, our study highlighted that 33.8% of participants believed that forgetting to take insulin injections was a leading cause of DKA, highlighting a serious misunderstanding of a major contributing risk factor.…”
Section: Discussioncontrasting
confidence: 76%
“…This variance could be attributed to the larger number of participants in our study compared to the Sudanese study. The study conducted in Riyadh [8] indicated that the most recognized symptoms of DKA were the characteristic smell of breath (70.0%) and vomiting (66.2%). The disparity in results might be because the researchers did not include extreme thirst and frequent urination as options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study done in Riyadh, KSA [ 17 , 18 ], 68.8% of diabetic caregivers were sure that DKA could lead to coma or severe dehydration (63.3%) with 88.9% who knew that DKA can be prevented by taking insulin as instructed. In our study, only a quarter (40.8%) were confident that for an incidence of DKA, the most important action to be taken was to rush the patient to the hospital to get immediate treatment; however, only 25.3% of our sample was aware that neglecting insulin shot could lead to DKA.…”
Section: Discussionmentioning
confidence: 99%
“…This imbalance leads to an excessive rise in body weight and fat mass, resulting in the accumulation of energy in the form of adipose tissue [1], [2]. Obesity increases the percentage of morbidity and mortality in humans because obesity is a factor in the emergence of cardiovascular disease, hypertension, type 2 diabetes mellitus, hypercholesterolemia, osteoporosis, depression, breast cancer, and colon cancer [3]. In addition, obesity can occur due to various factors, namely excessive food intake, lack of physical activity, technological advances to genetic factors.…”
Section: Introductionmentioning
confidence: 99%